2006
DOI: 10.1093/cercor/bhl001
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Activity at Rest Predicts Cochlear Implantation Outcome

Abstract: The functional status of central neural pathways, in particular their susceptibility to plasticity and functional reorganization, may influence speech performance of deaf cochlear implant users. In this paper, we sought to determine how brain metabolic activity measured before implantation relates to cochlear implantation outcome, that is, speech perception. In 22 prelingually deaf children between 1 and 11 years, we correlated preoperative glucose metabolism as measured by F-18 fluorodeoxyglucose positron emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
158
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(182 citation statements)
references
References 49 publications
19
158
0
3
Order By: Relevance
“…Further downstream, cochlear inactivation can lead to atrophic changes (such as reductions of neurons' soma areas or synaptic densities) in the SOC, the nucleus of the lateral lemniscus and the central nucleus of the inferior colliculus (Nishiyama et al 2000;Shepherd and Hardie 2001). Imaging studies have shown that, without activity from lower centres of the auditory system, the auditory cortex undergoes crossmodal plasticity, whereby other sensory modalities (particularly vision) take-over areas of the cortex normally specialized for hearing (reviewed in Lee et al 2001;Lee et al 2007). Studies using the deaf white cat as a model for congenital deafness have indicted that these animals have decreased spiral ganglion cell density, decreased cell size in the MSO, and decreased number and size of synaptic terminals in the MSO (Schwartz and Higa 1982).…”
Section: The Deaf Auditory Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Further downstream, cochlear inactivation can lead to atrophic changes (such as reductions of neurons' soma areas or synaptic densities) in the SOC, the nucleus of the lateral lemniscus and the central nucleus of the inferior colliculus (Nishiyama et al 2000;Shepherd and Hardie 2001). Imaging studies have shown that, without activity from lower centres of the auditory system, the auditory cortex undergoes crossmodal plasticity, whereby other sensory modalities (particularly vision) take-over areas of the cortex normally specialized for hearing (reviewed in Lee et al 2001;Lee et al 2007). Studies using the deaf white cat as a model for congenital deafness have indicted that these animals have decreased spiral ganglion cell density, decreased cell size in the MSO, and decreased number and size of synaptic terminals in the MSO (Schwartz and Higa 1982).…”
Section: The Deaf Auditory Systemmentioning
confidence: 99%
“…Previous literature has suggested that electrical stimulation delivered from within the cochlea may help to prevent some of the degeneration normally caused by profound SNHL (Leake et al 2008;Vollmer et al 2005). For example, in order to diminish cross-modal takeover, children are often provided with cochlear implants as early as possible; so as to best promote speech perception performance (Lee et al 2007). Moreover, evoked potential studies have shown that the deaf and immature auditory brainstem retains the ability to change in response to prolonged stimulation from a single cochlear implant .…”
Section: Figure 14 the External Components Of A Cochlear Implantmentioning
confidence: 99%
See 1 more Smart Citation
“…The right posterior superior temporal gyrus/supramarginal gyrus (PSTG/SMG) undergoes a profound reorganization during deafness that is manifest in a hypermetabolism at rest [Giraud and Lee, 2007;Lee et al, 2007a], and in abnormal activation levels during visual speech tasks (rhyming and lip-reading tasks) [Lazard et al, 2010b;Lee et al, 2007b]. We previously argued that the involvement of this region in visually driven speech processing may be maladaptive, as it predicts poor phonological scores in deaf subjects and poor auditory speech perception after receiving a CI [Lazard et al, 2010b].…”
Section: Introductionmentioning
confidence: 99%
“…The reason why age has an important prognostic value is associated with brain plasticity; that is, age itself independently is not a major determinant, but rather, prelingual auditory deprivation, which causes brain plasticity, is. A low metabolic rate in the temporal cortices before CI is related to a more favorable speech perception outcome after CI [3][4][5][6] . There is controversy regarding functional reorganization in postlingual deaf adults [7] because the adult brain has already completed functional organization.…”
Section: Introductionmentioning
confidence: 99%